2023
DOI: 10.1007/s11282-023-00683-w
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of peri-implant bone defects by using cone beam computed tomography (CBCT): an integrative review

Abstract: The objective of this work was to perform an integrative review of the inspection of peri-implant bone defects using cone beam computed tomography (CBCT). An electronic search was performed in the PubMed database using the following scientific terms: CBCT or Cone Beam computed tomography; dental implant; peri-implant; bone loss; defects. The survey identified 267 studies, of which 18 were considered relevant to this study. These studies provided important data taking into account the accuracy of cone beam comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In the case of peri-implant bony defects, this means the three-dimensional extent of the defect and the parts that are located buccaly or orally to the implant, as well as revealing fenestration and dehiscence defects, might be better depicted [16,17]. Studies by Ritter et al and Steiger-Ronay et al concluded that measurements of distal and mesial bone levels are equally accurate with intraoral radiography and CBCT [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of peri-implant bony defects, this means the three-dimensional extent of the defect and the parts that are located buccaly or orally to the implant, as well as revealing fenestration and dehiscence defects, might be better depicted [16,17]. Studies by Ritter et al and Steiger-Ronay et al concluded that measurements of distal and mesial bone levels are equally accurate with intraoral radiography and CBCT [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…In 1998, Mozzo et al introduced cone beam imaging technology, which, depending on the specific configurations of the cone beam computerized tomography (CBCT) unit, allows three-dimensional images to be obtained with relatively low radiation doses [ 17 ]. Although CBCT has made a speedy ingress into the field of dentistry, it is not devoid of downsides, as the image’s clarity is affected by artifacts, noise, and poor soft tissue contrast [ 18 ].…”
Section: Introductionmentioning
confidence: 99%